Systematic family‐wide analysis of sodium bicarbonate cotransporter NBCn1/SLC4A7 interactions with PDZ scaffold proteins. Issue 5 (20th May 2014) - Lee, Hye Jeong; Kwon, Min Hyung; Lee, Soojung; Hall, Randy A.; Yun, C. Chris; Choi, Inyeong
Abstract NBCn1 (SLC4A7) plays a role in transepithelial HCO3− movement and intracellular pH maintenance in many tissues. In this study, we searched PDZ proteins capable of binding to NBCn1. We screened a protein array membrane, on which 96 different class I PDZ protein peptides were blotted, with the C‐terminal domain of NBCn1 fused to GST. Thirteen proteins were identified in these screens: MAGI‐3, NHERF‐1, NHERF‐2, PSD‐95, chapsyn‐110, ERBIN, MALS‐1, densin‐180, syntrophins α1, β2, γ2, MUPP1, and PDZK1. After determining these binding partners, we analyzed the database of known and predicted protein interactions to obtain an NBCn1 interaction network. The network shows NBCn1 being physically and functionally associated with a variety of membrane and cytosolic proteins via the binding partners. We then focused on syntrophin γ2 to examine the molecular and functional interaction between NBCn1 and one of the identified binding partners in the Xenopus oocyte expression system. GST/NBCn1 pulled down syntrophin γ2 and conversely GST/syntrophin γ2 pulled down NBCn1. Moreover, syntrophin γ2 increased intracellular pH recovery, from acidification, mediated by NBCn1's Na/HCO3 cotransport. Syntrophin γ2 also increased an ionic conductance produced by NBCn1 channel‐like activity. Thus, syntrophin γ2 regulates NBCn1 activity. In conclusion, this study demonstrates that NBCn1 binds to many PDZ proteins, which in turn may allow the transporter to associate with other physiologically important proteins.